Penguatan Karakter Kepemimpinan Siswa melalui Latihan Dasar Kepemimpinan OSIS di SMP Satu Atap Margabakti - Agustira, Deden; Rudiansyah, Parman; Rahmat, Hamidan (Yayasan Dekhalisha Global Prestise, 2026)
The Basic Leadership Training (Latihan Dasar Kepemimpinan/LDK) represents a strategic capacity-building program designed to cultivate leadership competencies, self-confidence, and organizational skills among students. This community service activity aimed to enhance the leadership competencies of the student council (OSIS) executive members at SMP Satu Atap Margabakti, Kadugede District, Kuningan Regency — a school situated in a remote rural area characterized by limited access to systematic student development programs. The activity was conducted over a full day (approximately eight hours), engaging 25 participants comprising active OSIS executive members, student representatives, and OSIS faculty advisors. The instructional approach employed participatory training grounded in experiential learning principles, encompassing: leadership theory enrichment, public speaking and oratory exercises, deliberative consensus (musyawarah mufakat) simulation, and group dynamics activities. Evaluation was conducted through a participant satisfaction questionnaire (13 items, four-point Likert scale) and structured observation utilizing a three-tier rubric. Evaluation outcomes indicated an overall satisfaction rate of 85% (classified as Highly Satisfied), with 68% of participants attaining the highest level of active participation and 56% demonstrating voluntary presentation readiness. The novelty of this initiative lies in the implementation of an integrated LDK model within a satu atap (combined-level) school in a remote area that had previously lacked access to systematic leadership development interventions. The activity is recommended for continuation on a minimum annual basis per academic year.